A Conceptual Framewok of Academic Integrity in Islam - Akbar, Akbar; Picard, MIchelle (Proceedings of International Conference on Muslim Society and Thought, 2024)
Academic integrity is vital to maintain quality standards and prevent misconduct that undermines standards in higher education institutions, including in Islamic Higher Education (IRHE) Institutions. However, this concept has been stereotyped as a western concept because the literature of academic integrity has flourished in western universities over the past three decades. This study aims to investigate the relationship between Islam and the concept of academic integrity and provides evidence that academic integrity should not be regarded as merely a Western concept but is also conceptualized in Islam. This study was designed using grounded theory. Muslim scholars in three IRHE institutions in Indonesia were interviewed to find out how they conceptualized academic integrity in Islam. The data were analyzed using content analysis and themes emerged to develop a conceptual framework of academic integrity in Islam. The study found that academic integrity and religiosity is intertwined. This study brings a new understanding that religiosity and academic integrity is inseparable in IRHE.